Implementasi Teologi Ekologi Dalam Praktik Jurnalisme Profetik Di Ayobandung - Maulana, Adi Ginanjar (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2025)
This study analyzes the implementation of ecological theology in prophetic journalism practice at AyoBandung, a local media platform grounded in social and religious values. Using a descriptive qualitative approach and thematic analysis, data were collected through interviews with eight editorial members and analysis of thirty environmental news articles. Findings reveal two main themes: first, prophetic ecological journalism emphasizing morality, spirituality, and social responsibility in environmental reporting; and second, digital ecology highlighting media’s role as a public faith space through digital participation. The study proposes a new conceptual model, Digital Ecological Communication Theology, integrating prophetic journalism (Parni Hadi), ecological theology (Dermot A. Lane), and networked theology (Heidi A. Campbell & Stephen Garner). This model demonstrates how faith, ecology, and technology can converge in digital media praxis to cultivate public ecological awareness in urban contexts.